Evaluation and quality in Higher Education: the impacts of the 1995-2002 period (Educação e Pesquisa, 2009)
The objective of this work consists in apprehending the impacts that the evaluation policy for Higher Education adopted during the 1995-2002 period had for the construction of the concept of quality in institutions of Higher Education, so as to understand its intrinsic logic. The methodological procedure adopted relied on the documental analysis of the results obtained with the evaluation system developed by the Ministry for Education - MEC - for undergraduate courses during the period under consideration here, which incorporated the following evaluation instruments: the National Courses Exam (Exame Nacional de Cursos); the peer evaluations carried out for the purpose of course accreditation; and statistical data. The analysis of the reports from evaluation committees followed the geographical criterion of selecting only evaluations conducted for the State of Mato Grosso do Sul. Results showed that since 1995 the evaluation process has been used as a mechanism for the expansion of courses and institutions, based on the establishment of different concepts of quality suited to the administrative organization of the institutions of Higher Education, crystallizing the existing variety constituted by universities, university centers, and colleges. Despite the positive impact of evaluation observed in the institutional sphere, the evidence gathered here points to the exhaustion of the power of evaluation to promote further improvements in the quality of education, since institutions have been seeking to comply with the formal aspects of the quality standards set up by MEC without actually changing the essential quality of the education they offer.